EFFECT OF PROBLEM SOLVING LEARNING MODEL AND UNDERSTANDING THE CONCEPT OF PHYSICS STUDENT LEARNING OUTCOMES - Apriani Sijabat; Motlan .; Derlina . (Jurnal Pendidikan Fisika, 2016)
This research aims to analyze the students’ problem solving ability in problem solving model and conventional learning, analyze the students’ problem solving ability between the students who have understanding the concept above the average and the students who have understanding below the average, and also analyze the interaction between the learning model and the understanding concept on the students’ problem solving ability. This research is quasi experiment. Sample selection was done by using random class technique twice, where the first class was taught problem solving model while the second class was taught conventional learning. The instrument which was used consisted of the tests of problem solving ability and test of understanding the concept. The data in this research was analyzed by using two way anova. The result of this research showed that the students’ problem solving ability who was taught problem solving model was better than the students’ problem solving ability who was taught conventional, the students’ problem solving ability with understanding the concept above the average showed a better result than the students with understanding the concept below the average, and there was an interaction between problem solving model and understanding the concept on the students’ problem solving ability